Secondary Effects and Public Morality - Legarre, Santiago (2017)
The police power consists of the authority of the state to regulate in the interests of public health, safety, and morals. As American society continues to grow more diverse and pluralistic, courts and commentators have raised concerns that the last of these, public morality, cannot serve as an acceptable justification for regulatory action. Indeed, if appeals to public morality cannot be evaluated on an objective basis, then regulators might invoke them to conceal unlawful motives. The ability of moral reasoning to provide a legitimate basis for regulation is thrown into doubt. In this Article, we examine a peculiar line of Supreme Court cases in the free speech context that bring the problem into focus. In the so-called secondary effects cases, the Justices gradually moved away from accepting public morality arguments in support of state restrictions on adult businesses. In place of public morality, the Court began to retrain its focus on the social ills attendant to the activity in question, or what it termed the ?secondary effects? of such conduct. Rather than decide whether the regulated activity is immoral, and thus within the legitimate regulatory sweep of the police power as traditionally conceived, the Court instead looked to whether the state could show that its restriction reduced deleterious secondary effects associated with the activity. This development might have appeared desirable insofar as it would permit courts to rest their rulings on objective facts rather than wrestle with matters of opinion and moral sentiment. To the contrary, we argue, secondary effects arguments rely on moral reasoning –whether articulated or not– to the same extent as public morality arguments. The Court?s attempt in the secondary effects cases to avoid engaging in moral reasoning in reality demonstrates its indispensability.